ChemInform Abstract: An Elusive Fulvene 1, 7, 11, 24‐C60(CF3)4 and Its Unusual Reactivity. Issue 13 (1st April 2014) - Whitaker, James B.; Kuvychko, Igor V.; Shustova, Natalia B.; Chen, Yu‐Sheng; Strauss, Steven H.; Boltalina, Olga V.
Abstract The X‐ray crystal structure of the title compound is reported for the first time.